Spatial Differences in the Latin American Health Transition - Jenny Garcia; France Meslé (Espace populations sociétés, 2024)
During the last century, Latin American countries experienced a rapid decrease in mortality rates and a shift in cause-of-death structure, marked by significant reductions in infectious and parasitic diseases. These mortality changes initially manifested in urban areas and progressed more rapidly in countries with higher levels of urbanization. At the end of the century, mortality decline slowed, and the increase in life expectancy showed signs of stagnation in some countries. This study investigates age-specific mortality trends and causes of death during the period 2000–2010, aiming to discern whether the slowdown represents an overall lack of progress or is concentrated within specific subpopulations. Given the historical positive correlation between urbanization and mortality decline in Latin America, we analyze five countries across three spatial groups: main and large cities (over 500,000 inhabitants); medium-sized and small cities (20,000 to 499,000 inhabitants); and towns/rural areas combined (under 20,000 inhabitants) in Brazil, Chile, Colombia, Mexico, and Venezuela. Principal component and hierarchical cluster analyses classify similarities and differences in age-specific mortality trends among spatial groups. Additionally, using the algorithm of the contour replacement decomposition method, we estimate age and cause-of-death contributions to differences in life expectancy at birth among subpopulations. Findings reveal a successful or ongoing transition in the most urbanized countries and spatial groups, juxtaposed with a failed or delayed transition in less urbanized areas. This period marks the end of the convergence cycle associated with a reduction in communicable diseases and declining cardiovascular mortality in ages 45 to 74. Simultaneously, a new cycle of divergence emerges, centered around mortality in older adult ages (75 years and above), driven by the greater effectiveness of the main and large cities in reducing cardiovascular disease lethality.